(untitled) (Lectio: Journal of Language and Language Teaching, 2026)
Politeness plays an important role in communication as it helps speakers maintain harmonious social relationships. This phenomenon is also reflected in movies through the language choices of characters. This study investigates the types of politeness strategies used by Solène in The Idea of You movie and explains the factors influencing her choice of strategies. A qualitative research method was employed in this study. The data were obtained from Solène’s utterances taken from selected scenes of the movie through subtitle observation. The collected data were analyzed by classifying the utterances based on politeness strategy types and identifying the factors that influenced their use. The findings reveal that Solène used all four types of politeness strategies, namely bald-on-record, positive politeness, negative politeness, and off-record strategies. Among these, positive politeness was the most frequently used strategy. In addition, two factors were found to influence Solène’s use of politeness strategies, namely the payoffs of politeness strategies and sociological variables. The results indicate that sociological variables were the most dominant factor affecting her choice of politeness strategies.